Cardio-renal protective effects of SGLT2 inhibitors in patients with type 2 diabetes mellitus and severely impaired renal function. (14th October 2021) - Kanai, M; Kimura, K; Motoki, H; Suzuki, S; Okano, T; Minamisawa, M; Yoshie, K; Kato, T; Saigusa, T; Ebisawa, S; Okada, A; Kuwahara, K
Abstract: Background: Prognostic impact of Sodium-Glucose Cotransporter 2 (SGLT2) inhibitors on cardiovascular and renal outcome was unknown in patients with type-2 diabetes mellitus (DM) and severely impaired renal function. Methods: From July 2015 to December 2020, patients with type-2 DM who were taken SGLT2 inhibitors for more than six months were retrospectively screened. Patients with estimated glomerular filtration rate (eGFR) over 60ml/min/1.73m 2 were excluded. We divided those patients into two groups by eGFR; less than 45ml/min/1, 73m 2 were group A and 46–60ml/min/m 2 were group B. Randomly selected patients with DM not taking SGLT2 inhibitors and having severe renal dysfunction: eGFR less than 45ml/min/m 2 (Group C) were set as controls. The primary outcome was a composite of cardiovascular/renal death, initiation of dialysis, doubling of the serum creatine level, decline in the eGFR more than 30%, nonfatal myocardial infraction, nonfatal stroke, and hospitalization for heart failure. Results: Totally 418 patients were enrolled. Median age was 71 years (group A, n=106), 64 years (group B, n=115), and 77 years (group C, n=201) (p<0.001). After median 24 months follow-up, primary endpoints were observed 24.5% in group A, 4.3% in group B, 36.8% in group C (p<0.001). In Kaplan-Meier analysis, significantly lower incidence of primary endpoints were observed in SGLT2 groups (group A and B) than controls (p<0.001, Figure 1). In patients with severe renal dysfunction, taking SGLT2 inhibitors tended to decrease future renal event (Figure 2). The incidence of SGLT2 related adverse events was not different between 2 groups (A and B). Conclusions: Even in patients with severe renal dysfunction, SGLT2 inhibitors would have cardio-renal protective effects without drug-related adverse effects. Funding Acknowledgement: Type of funding sources: None.